2015
DOI: 10.1093/bjsw/bcv094
|View full text |Cite
|
Sign up to set email alerts
|

How Social Work Can Contribute in the Shift to Personalised, Recovery-Oriented Psycho-Social Disability Support Services

Abstract: This paper presents the findings from an Australian study in which forty-one people, who self-identified as having a psychosocial disability as a result of mental health problems, spoke about their priorities for treatment, care and support within a personalised funding context. The research enabled an improved understanding of the choices about support that people with psychosocial disabilities would make if offered individualised funding packages. Participant's prioritised specific supports to improve their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 24 publications
2
40
0
2
Order By: Relevance
“…Some of the core tasks at facilities providing inpatient SUD treatment include promoting change and development [ 30 , 31 , 32 ]. Environmental factors that have been shown to foster positive change (i.e., contextual psychosocial factors that enable development, satisfaction and well-being) include user involvement and empowerment, diversity of treatment options, individualised treatment measures, and the opportunity to pursue individually defined goals [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the core tasks at facilities providing inpatient SUD treatment include promoting change and development [ 30 , 31 , 32 ]. Environmental factors that have been shown to foster positive change (i.e., contextual psychosocial factors that enable development, satisfaction and well-being) include user involvement and empowerment, diversity of treatment options, individualised treatment measures, and the opportunity to pursue individually defined goals [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…From observations of this approach, this perspective of the recovery process can be, and often is, paternalistic in nature. For example, Brophy et al (2015) highlight that participants observed mental health challenges as long term, citing these challenges as ongoing psychosocial disabilities that participants expected to continue over a prolonged period. The effects of such disability are substantial, with Brophy et al (2015) categorising them under three tiers: life-long learning activities, social interactions and employment.…”
Section: Recovery Definitionsmentioning
confidence: 99%
“…For example, Brophy et al (2015) highlight that participants observed mental health challenges as long term, citing these challenges as ongoing psychosocial disabilities that participants expected to continue over a prolonged period. The effects of such disability are substantial, with Brophy et al (2015) categorising them under three tiers: life-long learning activities, social interactions and employment. Each can cause service users to become more insular, creating an isolating and stigmatising environment, which serves as a negative loop.…”
Section: Recovery Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents additional supports and is not a substitute for clinical care by mental health providers in hospital and community. Mental health social workers will form a large component of the rapidly expanding disability workforce and will need to consider what they have to offer such a scheme and how to support increased choice and control by people like John (Brophy et al, 2015).…”
Section: The Mental Health Social Work Rolementioning
confidence: 99%